Zambia Jobs Diagnostic : Policy Framework - Krishnan, Sudha Bala; Merotto, Dino; Peterburs, Teresa; Walker, David Ian (World Bank, Washington, DC, 2017)
Jobs need to be at the heart of economic development policies in Zambia. Recognizing the role of jobs in making Zambia a more equal middle-income country, the Government of Zambia has prioritized job creation in its Vision 2030 and National Strategy on Job Creation and Industrialization by setting a goal to create one million jobs in key sectors over the next five years. This report has three main objectives. First, it outlines the main challenges to Zambia's jobs agenda at the macro, household, and firm levels. Second, it takes a closer look at jobs at a sectoral level, with a focus on agribusiness value chains that illustrates the potential for job creation in high-potential sectors. Lastly, it presents a set of policies that may be prioritized by policymakers as part of implementing a jobs strategy through creating more formal sector jobs, improving the quality of informal sector jobs, and connecting vulnerable population groups to jobs.